2011
DOI: 10.1136/vr.c6106
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coxiella burnetii infection in Dutch dairy herds based on testing bulk tank milk and individual samples by PCR and ELISA

Abstract: A study using an ELISA and a real-time PCR assay based on the detection of the repetitive transposon-like gene of Coxiella burnetii revealed that infection with the bacterium was widespread among Dutch dairy herds, with antibodies detected in bulk tank milk (BTM) from 268 of 341 herds (78.6 per cent) and bacterial DNA detected in 193 of 341 herds (56.6 per cent). The BTM samples were taken in November and December 2007. Serological and molecular studies in young and adult cattle selected from 100 herds showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 15 publications
11
96
3
1
Order By: Relevance
“…However, studies of frequency of infection in ruminants based on PCR analysis are uncommon 23 and this knowledge is important to determine the risk of transmission between animals and from animals to humans 5 . In the present study, 6% (n=4) of 66 sheep's milk and 0.6% (n=2) of 328 vaginal swabs from goats yielded C. burnetii DNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of frequency of infection in ruminants based on PCR analysis are uncommon 23 and this knowledge is important to determine the risk of transmission between animals and from animals to humans 5 . In the present study, 6% (n=4) of 66 sheep's milk and 0.6% (n=2) of 328 vaginal swabs from goats yielded C. burnetii DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The serological and molecular studies performed in the herds, where antibodies were present in blood of lactating cows, showed that Coxiella burnetii DNA was detected in the milk (8.7%). The antibodies were detected only in the serum of 1 % of young cattle selected from these herds (Muskens, 2011).…”
Section: Zoonotic Aspectsmentioning
confidence: 99%
“…PCR assays in south-west England disclosed that the prevalence of C. burnetii in herd was 69.7% (34) and serological analyses of BTM samples in northern Spain revealed that 67% of dairy cattle herds were seropositive and that C. burnetii DNA was present in 52% of the herds (1). Muskens et al (25) reported that in the Netherlands 78.6% of Dutch herds tested had antibodies against C. burnetii in BTM, out of the tested animals 56.6% presented detectable bacterial DNA. Studies conducted in Belgium revealed positive PCR results to 30% of BTM samples, while the prevalence of C. burnetii in BTM in the UK was 69.7% for PCR (8,33).…”
Section: Prevalence Of C Burnetii In Ruminantsmentioning
confidence: 99%
“…However, according to the available literature data, the examination of environmental samples is an important additional diagnostic step (27). It should be noted that the presence of C. burnetii in bovine faecal samples is noted very rarely, so faeces should not be included in sampling protocols described to evaluate C. burnetii in bovine herds (25). Dust from surfaces, air, or slurry are appropriate environmental samples for identification of the infection status.…”
Section: Shedding Of C Burnetiimentioning
confidence: 99%